El Duce envía refuerzos : (Diciembre 1936) / [redacción Javier Redondo... (et al.)] - Redondo Rodelas, Javier (La guerra civil Española mes a mes ; 8)
Contiene "Semblanzas" de : Melchor Rodríguez, Belarmino Tomás, Martínez Monge, Don Juan de Borbon, Manuel Fal Conde, Miguel de Unamuno, Diego Abad de Santillán